The Effects of Carbonation and Elevated Temperatures on the Properties of Magnesium-Based Mortar - Aytimur, Neslisah; Ulukaya, Serhan; Akca, Abdullah Huzeyfe (MDPI, 2025)
Reactive MgO cement can substitute Portland cement in constructions for numerous purposes. While hydration of MgO yields a low-strength material, incorporation of additives, CO2 and heat curing can improve strength development. This study highlights how curing conditions and additives affect reactive MgO cements under elevated temperatures, providing key insights for enhancing sustainable construction materials with lower carbon footprints. Therefore, mortar mixtures were carbonated in a CO2 incubator for 3-14 days utilizing reactive MgO cement as a binder. Sodium carbonate and sodium bicarbonate were separately incorporated into mixtures to investigate their influence on compressive strength and microstructure. Elevated temperatures were also tested on carbonated magnesium-based material. Carbon dioxide curing enhanced compressive strengths and the reference carbonated group reached 20.1 MPa at the 14th day of curing. Sodium carbonate reduced the hydration rate and compressive strength, while air-cured mortar with sodium carbonate solution had the lowest compressive strength. However, sodium bicarbonate increased the strength of air-cured specimens. The specimens heated to 50 degrees C demonstrated a 35% increase in compressive strength, while temperatures of 100 degrees C or above led to a decline in strength. Hydration of MgO produced brucite and carbonation formed dypingite in the specimens' microstructure. Temperature rise led to the disintegration of dypingite and rthe reappearanceof MgO.
Keywords: reactive MgO cement; carbonation; elevated temperatures; microstructure; MECHANICAL-PROPERTIES; MGO CONCRETE; PERFORMANCE; HYDRATION; Chemistry; Engineering; Materials Science; Physics